2018
DOI: 10.1002/pca.2762
|View full text |Cite
|
Sign up to set email alerts
|

UPLC‐Q‐TOF‐MS/MS‐guided dereplication of Pulsatilla chinensis to identify triterpenoid saponins

Abstract: This study provides an efficient analysis strategy to rapidly identify the triterpenoid saponins in Pulsatilla species even in traditional Chinese medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…The analytical results of the sample showed the four‐step mining strategy was suitable for analyzing the major compounds in AF. Meanwhile, the fragmentation behavior discovered in this study has been widely found in other triterpenoid saponins of TCMs . So, the four‐step strategy could be applied in further research of AF and other TCMs.…”
Section: Discussionmentioning
confidence: 54%
“…The analytical results of the sample showed the four‐step mining strategy was suitable for analyzing the major compounds in AF. Meanwhile, the fragmentation behavior discovered in this study has been widely found in other triterpenoid saponins of TCMs . So, the four‐step strategy could be applied in further research of AF and other TCMs.…”
Section: Discussionmentioning
confidence: 54%
“…Hederacoside C (3‐[{2‐ O ‐(α‐ l ‐rhamnopyranosyl)‐α‐ l ‐arabinopyranosyl}oxy]‐23‐hydroxyolean‐12‐en‐28‐oicacid6‐ O ‐{4‐ O ‐(α‐ l ‐rhamnopyranosyl)‐β‐ d ‐glucopyranosyl}‐β‐ d ‐glucopyranosyl ester, HDC) is a chief bioactive natural triterpenoid saponin . It is not only widely found in the Pulsatilla Adans , but also existed in the Hedera helix .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, electrospray ionisation quadrupole time‐of‐flight mass spectrometry (ESI‐Q‐TOF‐MS) has been used to identify plant metabolites owing to sensitivity and selectivity being superior to those of UV and ELSD. ESI‐Q‐TOF‐MS provides a reliable and exact mass of the target compound, which facilitates the prediction of the molecular formula and identification of saponins from plant extracts such as Panax ginseng , Pulsatilla chinensis , and Ilex pibescens …”
Section: Introductionmentioning
confidence: 99%
“…ESI-Q-TOF-MS provides a reliable and exact mass of the target compound, which facilitates the prediction of the molecular formula and identification of saponins from plant extracts such as Panax ginseng, Pulsatilla chinensis, and Ilex pibescens. [12][13][14][15] In this study, HPLC-ESI-Q-TOF-MS was used to profile the saponin composition of an enriched saponin extract of C. japonica seeds (CJ-ESE). For the systematic separation of saponins, high-performance countercurrent chromatography (HPCCC) was applied to yield saponin fractions in the order of the number of sugars attached to the triterpene aglycone (di-, tri-, and tetra-saccharides) from the CJ-ESE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation